Distributed concurrent linear logic programming - Kobayashi, Naoki; Shimizu, Toshihiro; Yonezawa, Akinori (Theoretical computer science, 1999)
We propose a framework of distributed concurrent linear logic programming, which can elegantly capture the essential features of distributed computation: location-dependence/independence of names and movement of computation. We first define the syntax and semantics of a modal linear logic that is suitable for expressing distributed computation, and then show that there is a close relationship between formulas of a fragment of the modal linear logic and distributed processes.